Specification for conference systems : electrical and audio requirements (BSI, 1989)
Conferences, Public-address systems, Communication equipment, Communication systems (buildings), Audio equipment, Microphones, Electrically-operated devices, Audio systems, Electronic equipment and components, Telecommunication systems, Telecommunication, Headphones, Assembly facilities, Definitions, Indicator lights, Colour, Performance, Control panels, Dimensions, Noise (spurious signals), Sensitivity, Magnetic field effects, Electrical properties and phenomena, Telecommunication links, Frequency response, Sound intensity, Signal distortion, Electrical impedance, Voltage, Electrical tolerances, Attenuation, Signal-to-noise ratio